Moon Girl and Devil Dinosaur. Full moon - Montclare, Brandon; Hadley, Amy Reeder, 1980- (Marvel Worldwide, Inc., 2019)
Compilation of comics in the Moon Girl and Devil Dinosaur series in which nine-year-old genius Lunella Lafayette recovers the Nightstone and meets Devil Dinosaur from the Savage Land who is hoping to recover it to keep it out of the hands of the Killer Folk. Lunella refuses to give it back and ends up befriending the dinosaur and taking on several enemies in the Marvel universe.